Entropy performance of nonlinear mathematical hydrocarbon based model using ternary alloys (AA7072/AA7075/Ti6AI4V) under influential solar radiations and convective effects - Mutasem Z. Bani-Fwaz; Adnan; Sami Ullah Khan; Zafar Mahmood; Yasir Khan; A. M. Obalalu; Mohammad Khalid Nasrat (Scientific Reports)
Abstract Aluminum alloys have promising characteristics which make them more useful in industrial applications for thermal management and entropy of the fluidic system. Hence, the current research deals with the analysis of entropy and thermal performance of (C2H6O2–H2O)/50:50% saturated by (AA7072/AA7076/Ti6AI4V) alloys. Traditional problem modified using enhanced characteristics of ternary alloys and hydrocarbon 50:50% base fluid. Further, significant effects of nonlinear solar radiations, dissipation and convective heat condition effects are also taken in the problem formulation. The developed model analyzed numerically and simulated the results for thermal performance, comparative entropy, shear drag and heat transfer rate. The results revealed that increasing the effects of dissipation energy, thermal radiations and temperature ratio number, the thermal performance of the system enhanced. However, magnetic effects are observed good to control the thermal boundary layer region. The ternary nanofluid showed dominant behavior followed $$\:B_{r}=\text{0.1,0.2,0.3,0.4}$$ and $$\:M=\text{0.1,0.2,0.3,0.4}$$ in the case of simple fluid which tells that more energy is unavailable to perform work. Further, the ternary nanofluid’s entropy shows that these fluids are more efficient due to cumulative thermal conductivity of (AA7072/AA7076/Ti6AI4V) alloys.